Vitamin K status in diabetic patients with chronic kidney disease stage 3-5 and its effects on chronic kidney disease - mineral bone disorder - S. Jayakumar,; Elena Azizan,; Shamsul Azhar Shah,; Arbaiyah Bain,; Abdul Halim Abdul Gafor, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Diabetic kidney disease (DKD) is common in Malaysia. Vitamin K deficiency among DKD patients may be associated with higher incidence of chronic kidney disease-mineral bone disorder (CKD-MBD). This study was conducted to determine the prevalence of vitamin K deficiency in diabetic patients with CKD stage 3-5. We also correlated vitamin K deficiency with baseline demographic, biochemical results and analysed the effects of vitamin K levels on CKD-MBD. This was a single centre cross-sectional study on diabetic patients with CKD stage 3-5. Demographic profiles were recorded, blood samples were measured for vitamin K level (phylloquinone, proteins induced by vitamin K absence II (PIVKA-II), prothrombin time) and bone markers (parathyroid hormone (PTH), alkaline phosphatase, corrected calcium and phosphate). This study was approved by UKM ethic and research committee (FF-2018-375). Forty-five patients with a median age of 70 (IQR:13) years were recruited. Majority were females (53.3%) and Malays (64.4%). Prevalence of patients with insufficient vitamin K was 28.9 % based on the low level of phylloquinone (<0.4 nmol/L), 93.3% based on high PIVKA-II level (>0.66 ng/mL) and 2.2% based on prolonged prothrombin time (>14.5 s). PIVKA-II was found to be positively correlated with serum creatinine and PTH levels. There were positive correlations between phylloquinone with serum triglyceride and total cholesterol. Prothrombin time was found to be negatively correlated with corrected calcium and total cholesterol. Malay race (p = 0.039) and high serum PTH (p = 0.016) were significantly associated with higher PIVKA-II concentrations. Multivariable analysis showed serum triglyceride (OR 0.112; CI 95 % (0.02-0.66); p = 0.017) and serum PTH (OR 1.997; CI 95 % (1.01-3.95); p = 0.047) were independent predictors for abnormal phylloquinone and PIVKA-II levels, respectively. In conclusion, the prevalence of Vitamin K deficiency was high in diabetic patients with CKD stage 3-5. Serum triglyceride and serum PTH were independent predictor of Vitamin K deficiency.